Popular Tv Fiction, Mediascape, And Malay Cultural Identities - Mohd Muzhafar Idrus; Ruzy Suliza Hashim; Raihanah M. M; Harison Mohd Sidek; Noor Saazai Mat Saad; Yurni Emilia Abdul Hamid; Suzanah Selamat; Hazleena Baharun (OCERINT International Organization Center of Academic Research, 2024)
Indexed by WOS